Understanding anti‐TNF treatment failure: does serum triiodothyronine‐to‐thyroxine (T3/T4) ratio predict therapeutic outcome to anti‐TNF therapies in biologic‐naïve patients with active luminal Crohn's disease?. Issue 5 (29th June 2022) - Lin, Simeng; Chanchlani, Neil; Carbery, Isabel; Janjua, Malik; Nice, Rachel; McDonald, Timothy J.; Bewshea, Claire; Kennedy, Nicholas A.; Ahmad, Tariq; Selinger, Christian P.; Goodhand, James R.; ,
Summary: Background: During illness, adaptations of the hypothalamic–pituitary‐thyroid axis reduce energy expenditure, protein catabolism and modulate immune responses to promote survival. Lower serum free triiodothyronine‐to‐thyroxine (fT3/fT4) ratio has been linked to non‐response to treatment in a range of diseases, including in biologic‐treated patients with inflammatory bowel disease. Aim: To assess whether baseline serum fT3/fT4 ratio predicted primary non‐response (PNR) and non‐remission to infliximab and adalimumab in patients with Crohn's disease Methods: Thyroid function tests were undertaken in stored serum from biologic‐naïve adult patients with active luminal Crohn's disease immediately prior to treatment with infliximab (427 originator; 122 biosimilar) or adalimumab (448) in the Personalised Anti‐TNF Therapy in Crohn's Disease study (PANTS). Results: Baseline median [IQR] fT3/fT4 ratios were lower in women than men (0.30 [0.27–0.34] vs 0.32 [0.28–0.36], p < 0.001), in patients with more severe inflammatory disease, and in patients receiving corticosteroids (0.28 [0.25–0.33] vs. 0.32 [0.29–0.36], p < 0.001). Multivariable logistic regression analysis demonstrated that fT3/fT4 ratio was independently associated with PNR at week 14 (odds ratio [OR] 0.51, 95% confidence interval [CI] 0.31–0.85, p = 0.009), but not non‐remission or changes in faecal calprotectin concentrations at week 54. The optimal threshold to determine PNR was 0.31 (area under the curve 0.57 [95% CI 0.54–0.61], sensitivity 0.62 [95% CI 0.41–0.74], and specificity 0.53 [95% CI 0.42–0.73]). Conclusions: Lower baseline serum fT3/fT4 ratio was associated with female sex, corticosteroid use and disease activity. It predicted PNR to anti‐TNF treatment at week 14, but not non‐remission at week 54. Abstract : In 995 patients with Crohn's disease from the PANTS study, lower baseline serum fT3/fT4 ratio was independently associated with female sex, higher inflammatory burden at baseline, and baseline corticosteroid use, and predicted primary non‐response to anti‐TNF therapy at week 14, but not non‐remission or change in faecal calprotectin concentrations at week 54. Overall, however, the diagnostic accuracy of baseline fT3/fT4 ratio to predict primary nonresponse to anti‐TNF treatment was modest, limiting its clinical utility.